QUALITY OF LIFE IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME: REQUISITE OF CLINICAL PHARMACIST INTERVENTION - RAMYA R; SHARON ANN JOSE; MAMATHA K; SURYA NARAYANA KM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Polycystic ovarian syndrome (PCOS) is a lifestyle disorder known to cause profound distress in the physical and emotional well-being of the patient that implicates the need for treatment and lifestyle management. Unawareness and ignorance among patients may be a predominant cause of compromised quality of life (QOL) that necessitates education from health-care professionals. The existing study was designed to assess the impact of counseling on QOL in the above patients. Methods: This hospital-based interventional study was carried out for 6 months. A total of 173 subjects were recruited for the study. The World Health Organization BREF, a validated, reliable tool to assess QOL was administered in two phases of the study, pre-interventional, and post-interventional phase. Awareness regarding disease and lifestyle modification were detailed by a clinical pharmacist to the patients, and its impact was assessed using suitable statistical techniques. Results: The average age of study participants was 23.9±4.5 years. Decreased QOL was observed in the women affected with PCOS when compared to healthy controls, wherein the psychological domain was the most affected. Post-intervention, a positive impact was reflected as higher scores in all the 4 QOL domains. Conclusion: Women suffering from PCOS exhibit varied symptoms which affect both physical and psychological health. The key factor in management is to create awareness on the complications of the disease and the lifestyle modification to minimize severity and progression. The study findings reveal that women with PCOS showed an improved QOL post participation in awareness programs imparted by the clinical pharmacists.